Activating charge-transfer state formation in strongly-coupled dimers using DNA scaffolds. Issue 44 (17th October 2022) - Hart, Stephanie M.; Banal, James L.; Castellanos, Maria A.; Markova, Larysa; Vyborna, Yuliia; Gorman, Jeffrey; Häner, Robert; Willard, Adam P.; Bathe, Mark; Schlau-Cohen, Gabriela S.
Abstract : DNA scaffolds enable the activation and suppression of photochemistry between strongly-coupled synthetic chromophores. Abstract : Strongly-coupled multichromophoric assemblies orchestrate the absorption, transport, and conversion of photonic energy in natural and synthetic systems. Programming these functionalities involves the production of materials in which chromophore placement is precisely controlled. DNA nanomaterials have emerged as a programmable scaffold that introduces the control necessary to select desired excitonic properties. While the ability to control photophysical processes, such as energy transport, has been established, similar control over photochemical processes, such as interchromophore charge transfer, has not been demonstrated in DNA. In particular, charge transfer requires the presence of close-range interchromophoric interactions, which have a particularly steep distance dependence, but are required for eventual energy conversion. Here, we report a DNA-chromophore platform in which long-range excitonic couplings and short-range charge-transfer couplings can be tailored. Using combinatorial screening, we discovered chromophore geometries that enhance or suppress photochemistry. We combined spectroscopic and computational results to establish the presence of symmetry-breaking charge transfer in DNA-scaffolded squaraines, which had not been previously achieved in these chromophores. Our results demonstrate that the geometric control introduced through the DNA can access otherwise inaccessible processes and program the evolution of excitonic states of molecular chromophores, opening up opportunities for designer photoactive materials for light harvesting and computation.